Lulworthinone, a New Dimeric Naphthopyrone From a Marine Fungus in the Family Lulworthiaceae With Antibacterial Activity Against Clinical Methicillin-Resistant Staphylococcus aureus Isolates - Jenssen, Marte; Rainsford, Philip; Juskewitz, Eric; Andersen, Jeanette H.; Hansen, Espen H.; Isaksson, Johan; Rämä, Teppo; Hansen, Kine Ø. (Frontiers in Microbiology, 2021)
The emergence of drug-resistant bacteria is increasing rapidly in all parts of the world, and the need for new antibiotics is urgent. In our continuous search for new antimicrobial molecules from under-investigated Arctic marine microorganisms, a marine fungus belonging to the family Lulworthiaceae (Lulworthiales, Sordariomycetes, Ascomycota) was studied. The fungus was isolated from driftwood, cultivated in liquid medium and studied for its potential of producing antibacterial compounds. Through bioactivity-guided isolation, a novel sulfated biarylic naphtho-α-pyrone dimer was isolated and its structure elucidated by spectroscopic methods, including 1D and 2D NMR and HRMS. The compound, named lulworthinone (1), showed antibacterial activity against reference strains of Staphylococcus aureus and Streptococcus agalactiae, as well as several clinical MRSA isolates with MICs in the 1.56-6.25 µg/ml range. The compound also had antiproliferative activity against human melanoma, hepatocellular carcinoma and non-malignant lung fibroblast cell lines, with IC50 values of 15.5, 27 and 32 µg/mL, respectively. Inhibition of bacterial biofilm formation was observed, but no eradication of established biofilm could be detected. No antifungal activity was observed against Candida albicans. During the isolation of 1, the compound was observed to convert into a structural isomer, 2, under acidic conditions. As 1 and 2 have high structural similarity, NMR data acquired for 2 was used to aid in the structure elucidation of 1. To the best of our knowledge, lulworthinone (1) represents the first new bioactive secondary metabolite isolated from the marine fungal order Lulworthiales.